2016
DOI: 10.2196/medinform.6433
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Web-Based Iranian Diabetic Personal Health Record App on Self-Care Status and Clinical Indicators: Randomized Controlled Trial

Abstract: BackgroundThere are 4 main types of chronic or noncommunicable diseases. Of these, diabetes is one of the major therapeutic concerns globally. Moreover, Iran is among the countries with the highest incidence of diabetic patients. Furthermore, library-based studies by researchers have shown that thus far no study has been carried out to evaluate the relationship between Web-based diabetic personal health records (DPHR) and self-care indicators in Iran.ObjectiveThe objective of this study is to examine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…2 Care is still suboptimal despite the fact that firm evidence exists about the optimal treatment of diabetes during the past decade. 3 Many patients with type 2 diabetes mellitus (T2DM) have difficulties reaching optimal blood glucose control. Nearly 50% of patients with diabetes have HbA1c levels above the recommended targets, 4 which has risen to 75% in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…2 Care is still suboptimal despite the fact that firm evidence exists about the optimal treatment of diabetes during the past decade. 3 Many patients with type 2 diabetes mellitus (T2DM) have difficulties reaching optimal blood glucose control. Nearly 50% of patients with diabetes have HbA1c levels above the recommended targets, 4 which has risen to 75% in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of numerous benefits suggested for consumers’ utilizing PHR systems [ 9 - 14 ], research has shown that such systems are not yet widely adopted or well known to consumers [ 9 , 10 , 15 - 23 ]. Bearing in mind the potential benefits of PHRs to consumers and their potential interest in these systems [ 11 , 24 , 25 ]—and that similar to any other type of information system (IS), adoption is a prerequisite for realizing the potential benefits of PHR systems [ 26 ]—research is needed to understand how to enhance adoption rates for PHR systems.…”
Section: Introductionmentioning
confidence: 99%
“…The largest group (n=34) consists of descriptive studies, both qualitative and quantitative [ 21 , 32 - 35 , 37 - 43 , 45 , 47 - 51 , 53 , 55 , 56 , 58 , 59 , 62 , 63 , 65 , 69 - 73 , 75 - 77 ]. The other 2 groups contain pre-post-test comparative studies [ 21 , 40 , 60 , 61 , 70 , 71 , 75 , 76 ] and studies comparing intervention and control groups [ 30 , 31 , 36 , 44 , 46 , 47 , 52 , 54 , 57 , 64 , 66 - 68 , 74 ]. The results of 7 mixed methods studies were divided and categorized according to the groups they best matched with [ 21 , 40 , 47 , 70 , 71 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the population demographics varied; most studies included a broad range of patients (eg, patients in hospitals [ 30 , 34 , 60 , 72 , 76 ] or in primary care [ 21 , 32 , 42 - 46 , 48 , 49 , 54 , 57 , 58 , 63 ]). Other studies focused on specific patient groups, like cancer patients [ 30 , 37 , 50 , 59 , 62 , 75 ], cardiac patients [ 40 , 66 , 74 ], chronically ill patients [ 31 , 64 , 71 ], HIV-positive patients [ 36 , 57 ], psychiatric patients [ 35 , 39 , 70 ], gynecologic patients [ 67 , 68 , 73 ], and veterans [ 35 , 36 , 39 , 55 , 56 , 69 , 77 ]. Ten studies investigated experiences of both patients and their care providers [ 21 , 32 , 34 , 40 , 51 , 57 , 58 , 60 , 70 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation